Planning for sustainable city tourism in the Netherlands - Nientied, Peter; Toto, Rudina (European Spatial Research and Policy, 2022)
The purpose of this paper is to examine policies and planning for sustainable city tourism in Amsterdam and Rotterdam and relate them to the notions of ‘tourism reset’ that emerged during the COVID pandemic period. Amsterdam is a prime European tourist city and has been suffering from problems associated with overtourism. Rotterdam receives much less tourists and can be seen as an emerging tourist city. Both cities have recently adopted new tourism policies, essentially future tourism visions. The case of Amsterdam and to a lesser extent that of Rotterdam show that formulating and agreeing on a tourism policy vision is easier than the decision-making process and implementing a vision. The instruments and powers of local government to manage the quantity and qualities of tourism are limited. Overtourism problems have stimulated carrying capacity thinking, which is considered inadequate for a multi-faceted problem like urban tourism.